5(7f-)=28(f-1)

Simple and best practice solution for 5(7f-)=28(f-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(7f-)=28(f-1) equation:



5(7f-)=28(f-1)
We move all terms to the left:
5(7f-)-(28(f-1))=0
We add all the numbers together, and all the variables
5(+7f)-(28(f-1))=0
We multiply parentheses
35f-(28(f-1))=0
We calculate terms in parentheses: -(28(f-1)), so:
28(f-1)
We multiply parentheses
28f-28
Back to the equation:
-(28f-28)
We get rid of parentheses
35f-28f+28=0
We add all the numbers together, and all the variables
7f+28=0
We move all terms containing f to the left, all other terms to the right
7f=-28
f=-28/7
f=-4

See similar equations:

| 15-35f=28-28f | | -20x+23-16x+13=180 | | 4u^2-23u-6=0 | | 3w(w)=72 | | 11x+1=3x-12 | | 7p+2=44 | | 1.5p-4=7 | | (1.018)^x=2 | | 7x-12=x+2+2x-3x= | | 2(5x–3)–3(2x–1)=9 | | 0=4t^2+9t-12 | | 3x-6=18+17x | | 5x29=2x233 | | 2x+6=3x+54 | | 5x29=23332x | | 7x+10=3x-18 | | x^2+5+2x=0 | | −20=p−16 | | 8x+1/8-4x/8=7 | | 2)6x+3)=18-3(16-3x) | | 3(x+1)+1+2x=-2(2x+2)+x | | -7(1-4m)=13(2m=3) | | -5-2r=1+2r | | 3k-4k=-4-2 | | -22x+11=33 | | -2/17/18+x=-4/133/198 | | 6x+(5-5x)21=20 | | -22x+11=11 | | 8n​-(5n+7​)=8 | | -217/18+x=-4133/198 | | -10+6x=12x+10 | | 7d​ =6 |

Equations solver categories